Simvastatin induces Foxp3(+) T regulatory cells by modulation of transforming growth factor-β signal transduction - Kim, Yong Chan (Blackwell Science Inc, 2010)
Statins are widely used drugs for the treatment of hypercholesterolaemia. A number of recent studies have suggested that statins also have pleiotropic effects on immune responses and statins have proven to be effective in the treatment of autoimmune diseases in animal models. Foxp3(+) T regulatory cells are a unique subset of CD4(+) T cells that mediate immunosuppression. Foxp3(+) T cells develop in the thymus, but can also be induced in peripheral sites in the presence of transforming growth factor-β (TGF-β). We demonstrate here that simvastatin blockade of the mevalonate pathway can mediate induction of mouse Foxp3(+) T cells and that simvastatin can synergize with low levels of TGF-β to induce Foxp3(+) T cells. The effects of simvastatin are secondary to a blockade of protein geranylgeranylation, are mediated at late time-points after T-cell activation, and are associated with demethylation of the Foxp3 promoter. One major effect of simvastatin was inhibition of the induction of Smad6 and Smad7, inhibitory Smads that inhibit TGF-β signalling. Our results suggest that one mechanism responsible for the immunosuppressive effects of statins is the ability to promote the generation of Foxp3(+) T regulatory cells.